1997
DOI: 10.1103/physrevlett.78.3749
|View full text |Cite
|
Sign up to set email alerts
|

Parity Effect in Ground State Energies of Ultrasmall Superconducting Grains

Abstract: We study the superconductivity in small grains in the regime when the quantum level spacing δε is comparable to the gap ∆. As δε is increased, the system crosses over from superconducting to normal state. This crossover is studied by calculating the dependence of the ground state energy of a grain on the parity of the number of electrons. The states with odd numbers of particles carry an additional energy ∆P , which shows non-monotonic dependence on δε. Our predictions can be tested experimentally by studying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
263
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(281 citation statements)
references
References 15 publications
(49 reference statements)
16
263
2
Order By: Relevance
“…RBT's new experiments stimulated a number of theoretical attempts to quantitatively describe the crossover from the bulk limit d ≪∆, where superconductivity is well-developed, to the fluctuation-dominated regime of d ≫∆, where pairing correlations survive only in the form of weak fluctuations. Describing this crossover constituted a conceptual challenge, since the standard grand-canonical mean-field BCS treatment of pairing correlations [21][22][23][24][25][26][27][28] breaks down for d ∆ . This challenge elicited a series of increasingly sophisticated canonical treatments of pairing correlations [33][34][35][36][37][38][39][40][41], based on a simple reduced BCS-Hamiltonian for discrete energy levels, which showed that the crossover is completely smooth, but, interestingly, depends on the parity of the number of electrons on the grain, as pointed out by von Delft et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…RBT's new experiments stimulated a number of theoretical attempts to quantitatively describe the crossover from the bulk limit d ≪∆, where superconductivity is well-developed, to the fluctuation-dominated regime of d ≫∆, where pairing correlations survive only in the form of weak fluctuations. Describing this crossover constituted a conceptual challenge, since the standard grand-canonical mean-field BCS treatment of pairing correlations [21][22][23][24][25][26][27][28] breaks down for d ∆ . This challenge elicited a series of increasingly sophisticated canonical treatments of pairing correlations [33][34][35][36][37][38][39][40][41], based on a simple reduced BCS-Hamiltonian for discrete energy levels, which showed that the crossover is completely smooth, but, interestingly, depends on the parity of the number of electrons on the grain, as pointed out by von Delft et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous works [2,3,4,6,7,8,9, 10] studied a half-filled band with fixed width 2ω D of uniformly-spaced levels (i.e. ε j = j d), containing N = 2n + b electrons.…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
“…and a parity parameter introduced by Matveev and Larkin (ML) [6] to characterize the even-odd ground state energy difference,…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
See 2 more Smart Citations